Development of Inhibitors of Human PCSK9 as Potential Regulators of LDL-Receptor and Cholesterol - Alghamdi, Rasha Hassen (Université d'Ottawa / University of Ottawa, 2014)
Proprotein Convertase Subtilisin/Kexin 9 (PCSK9) is the ninth member of the Ca+2-dependent mammalian proprotein convertase super family of serine endoproteases that is structurally related to the bacterial subtilisin and yeast kexin enzymes. It plays a critical role in the regulation of lipid metabolism and cholesterol homeostasis by binding to and degrading low-density lipoprotein-receptor (LDL-R) which is responsible for the clearance of circulatory LDL-cholesterol from the blood. Owing to this functional property, there is plenty of research interest in the development of functional inhibitors of PCSK9 which may find important biochemical applications as therapeutic agents for lowering plasma LDL-cholesterol. The catalytic domain of PCSK9 binds to the EGF-A domain of LDL-R on the cell surface to form a stable complex and re-routes the receptor from its normal endosomal recycling pathway to the lysosomal compartments leading to its degradation. Owing to these findings, we propose that selected peptides from PCSK9 catalytic domain, particularly its disulphide (S-S) bridged loop1 323-358 and loop2 365-385, are likely to exhibit strong affinity towards the EGF-A domain of LDL-R. Several regular peptides along with corresponding all- dextro and retro-inverse peptides as well as the gain-of-function mutant variants were designed and tested for their regulatory effects towards LDL-R expression and PCSK9-binding in human hepatic HepG2 and mouse hepatic Hepa1c1c7 cells. Our data indicated that disulfide bridged loop1-hPCSK9323-358 and its H357 mutant as well as two short loop2-hPCSK9372-380 and its Y374 mutant peptides modestly promote the LDL-R protein levels. Our study concludes that specific peptides from the PCSK9 catalytic domain can regulate LDL-R and may be useful for development of novel class of therapeutic agents for cholesterol regulation.
Keywords: Proprotein Convertase Subtilisin/Kexin 9; PCSK9; Low Density Lipoprotein Receptor; LDL-R; Low Density Lipoprotein Cholesterol; LDL-C; Cardiovascular Disease; CVD; Autosomal Dominant Hypercholesterolemia; ADH; Catalytic Domain; Inhibitors; Peptides Design; LDL-R Degradation; Epidermal Growth Factor like repeat A; EGF-A; Familial Hypercholesterolemia; FH; Gain-of-Function Mutations